Influence of Annealing and Sintering on the Thermoelectric and Mechanical Properties of Gas Atomized p-type Skutterudites. (2015) - Schmitz, Andreas; Schmid, Carolin; de Boor, Johannes; Stiewe, Christian; Müller, Eckhard
Abstract: Filled cobalt-antimony based skutterudites are very promising thermoelectric materials for generator applications in an intermediate temperature range between 150 and 550 °C. For applications, besides the functional thermoelectric properties also the mechanical properties and production methodsplay an important role. Both thermoelectric and mechanical properties can be varied by adjusting the doping level, filling elements and filling fraction. Furthermore, the properties can be influenced by the choice of preparation routes leading to the formation of certain nano- or microstructures. In this work we investigate the influence of powder treatment and sintering temperature on the properties of p-type In0.2 Fe0.28 Co3.72 Sb12 skutterudites synthesized by gas atomization. After atomization the powder contains a large fraction of secondary phases which transform into the skutterudites phase during short term sintering. This phase transformation supports compaction and sintering. It is shown that the sintering temperature influences the resulting thermoelectric properties beyond pure effects of porosity. Best thermoelectric material propertiesare achieved at sintering temperatures between 550 and 600 °C. Annealing the atomized powder prior to sintering leads to phase pure material for which the sintering temperature only influences the thermoelectric properties via the resulting sample porosity.